2021
DOI: 10.1123/ijspp.2020-0799
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Recovery Strategies in Professional Soccer: A Worldwide Survey

Abstract: Purpose: To survey soccer practitioners’ recovery strategy: (1) use, (2) perceived effectiveness, and (3) factors influencing their implementation in professional soccer. Methods: A cross-sectional convenience sample of professional soccer club/confederation practitioners completed a web-based survey (April to July 2020). Pearson chi-square and Fisher exact tests with Cramer V (φ − c) assessed relationships and their strength, respectively, between the perceived effectiveness and frequency of strategy use. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…Accordingly, participants reported that the excessive cost and lack of devices/facilities were the main barriers to the use of recovery strategies. These findings are in agreement with previous research ( Simjanovic et al, 2009 ; Rey et al, 2018 ; Field et al, 2021 ), as accessibility has been frequently reported as a barrier to the implementation of recovery strategies. Therefore, it was expected that recovery strategies which are expensive and/or require specific facilities (e.g., cryotherapy, pool recovery, contrast water therapy and recovery/sleep devices) would be used relatively rarely, despite being often perceived as useful.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, participants reported that the excessive cost and lack of devices/facilities were the main barriers to the use of recovery strategies. These findings are in agreement with previous research ( Simjanovic et al, 2009 ; Rey et al, 2018 ; Field et al, 2021 ), as accessibility has been frequently reported as a barrier to the implementation of recovery strategies. Therefore, it was expected that recovery strategies which are expensive and/or require specific facilities (e.g., cryotherapy, pool recovery, contrast water therapy and recovery/sleep devices) would be used relatively rarely, despite being often perceived as useful.…”
Section: Discussionsupporting
confidence: 93%
“…Somewhat surprisingly, only a minority (27%) of the participants indicated lack of time as a barrier, while previous studies in other sports identified it as a major obstacle ( Simjanovic et al, 2009 ; Rey et al, 2018 ; Fullagar et al, 2019 ). Players’ negative perception of recovery strategies was mentioned as a possible barrier by a similar proportion of the participants (25%), supporting the notion that players preferences may not match scientific recommendations ( Crowther et al, 2017 ; Field et al, 2021 ). Efficient communication and education of players about the methods, tools and rationale supporting evidence-based interventions is crucial in order to effectively implement sound, effective practice ( Le Meur and Torres-Ronda, 2019 ; Field et al, 2021 ).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Mechanical compression, known as Intermittent pneumatic compression (IPC), has become increasingly popular in recent years, especially in athletes. A recent survey on professional soccer practitioners revealed that intermittent pneumatic compression was adopted by 57% of the teams surveyed [ 8 ]. The underlying assumption is that IPC increases blood circulation,, thus allowing for a faster regeneration due to improved tissue fluid exchange [ 9 ].…”
Section: Introductionmentioning
confidence: 99%